1977
DOI: 10.1111/j.1600-0536.1977.tb03692.x
|View full text |Cite
|
Sign up to set email alerts
|

Turpentine‐induced hypersensitivity to peppermint oil

Abstract: After a dental operation a former laboratory technician was referred to our clinic because of swelling of his tongue, lips, and gingival mucosa. Patch testing with the ICDRG standard test battery gave positive reactions to colophony, balsam of Peru, and turpentine peroxides. Further patch testing revealed hypersensitivity to peppermint oil (an ingredient of several dental preparations) due to the sensitizing properties of three ingredients: alpha-pinene, limonene, and phellandrene. These compounds also occur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 9 publications
0
17
1
1
Order By: Relevance
“…420 eczematous patients (37%) and 103 (63%) stasis dermatitis patients showed at least one positive 1 Certain substances were added to the 1CDRG standard test battery: benzocaine, chino-mix -chinoform and chlorquinaldol -abietic acid, coal tar, sulphanilamide, and promethazine. These additions and the pharmaceutical test series [6] were proposed by the Belgian Contact Dermatitis Group consisting of the Departments of Dermatology of the Katholieke Universiteit Leuven (H. Degreef), the Université Catholique de Louvain (J.M .Lachapelle), and the Université Libre de Bruxelles (J.Oleffe).…”
Section: Resultsmentioning
confidence: 99%
“…420 eczematous patients (37%) and 103 (63%) stasis dermatitis patients showed at least one positive 1 Certain substances were added to the 1CDRG standard test battery: benzocaine, chino-mix -chinoform and chlorquinaldol -abietic acid, coal tar, sulphanilamide, and promethazine. These additions and the pharmaceutical test series [6] were proposed by the Belgian Contact Dermatitis Group consisting of the Departments of Dermatology of the Katholieke Universiteit Leuven (H. Degreef), the Université Catholique de Louvain (J.M .Lachapelle), and the Université Libre de Bruxelles (J.Oleffe).…”
Section: Resultsmentioning
confidence: 99%
“…Terpenes, especially 3-carene, may irritate the skin and mucous membranes [8,9] and prolonged exposure may result in allergic contact dermatitis [10,11] or chronic lung function impairment [4], The active component may be an oxidation product, identified as a hydroperoxide of 3-carene [2,12]. The purpose of this study was to clarify the mechanism(s) of acute lung effects induced by 3-car ene using an isolated, perfused and ventilated guinea pig lung model.…”
Section: Introductionmentioning
confidence: 99%
“…Maibach [15] described a case of acute laryngeal obstruction probably due to delayed hypersensitivity to thiomersal. Dooms-Goossens et al [5] reported on a case of angio-oedema by peppermint oil with positive patch tests to this material.…”
mentioning
confidence: 99%